Active to sterile neutrino mixing limits from neutral-current interactions in MINOS - Adamson, P; Auty, D; Ayres, D; Backhouse, C; Barr, G; Bishai, M; Blake, A; Bock, G; Boehnlein, D; Bogert, D; Cavanaugh, S; Cherdack, D; et al. (2011)
Results are reported from a search for active to sterile neutrino oscillations in the MINOS long-baseline experiment, based on the observation of neutral-current neutrino interactions, from an exposure to the NuMI neutrino beam of 7.07×1020 protons on target. A total of 802 neutral-current event candidates is observed in the Far Detector, compared to an expected number of 754±28(stat)±37(syst) for oscillations among three active flavors. The fraction fs of disappearing νμ that may transition to νs is found to be less than 22% at the 90%C.L.